'The lady is not returning!*': educational precarity and a social haunting in the UK coalfields. Issue 2 (3rd May 2016) - Bright, N. Geoffrey
Abstract : Drawing on research in de-industrialised coal-mining communities in the north of England, this article focuses on how experiences of some young people might be approached through a notion of precarity linked to the idea of a 'social haunting' of the coalfields. Concentrating on data gathered in the period after the 2010 change of UK government, the article considers how localities suffering under the impact of 'austerity' measures have also witnessed moments of vivid, carnivalesque resurgence linked to celebrations of the death of former British Prime Minister Margaret Thatcher in April 2013 and of the thirtieth anniversary of the 1984–1985 UK miners' strike during 2014–2015. These celebrations mark a watershed in the cultural and affective life of the communities, one aspect of which relates to how young people with very different educational trajectories have become involved alongside each other in those events as a result of their different experiences of precarity.